2010
DOI: 10.1111/j.1440-1843.2010.01776.x
|View full text |Cite
|
Sign up to set email alerts
|

Heart failure and COPD: Partners in crime?

Abstract: Chronic obstructive pulmonary disease (COPD) and heart failure (HF) are both common diseases with major impact and seem to coexist more frequently than expected from their separate population prevalences. However, estimates of combined prevalence must be interpreted carefully because of imperfections and difficulties in assessment of both diseases. This review aims to highlight HF prevalence in patients with COPD and vice versa, with a critical analysis of studies performed. First, definition, diagnosis, and p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
20
1
4

Year Published

2012
2012
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(26 citation statements)
references
References 71 publications
1
20
1
4
Order By: Relevance
“…Like cardiovascular diseases, there is evidence that suggests that stable COPD is associated with low grade systemic inflammation 12. The risk of underlying ischemic heart disease is greater in patients with moderate or severe airflow obstruction and high circulating C-reactive protein (CRP), suggesting a certain influence of this inflammatory marker on cardiac risk.…”
Section: Pathophysiologymentioning
confidence: 99%
See 2 more Smart Citations
“…Like cardiovascular diseases, there is evidence that suggests that stable COPD is associated with low grade systemic inflammation 12. The risk of underlying ischemic heart disease is greater in patients with moderate or severe airflow obstruction and high circulating C-reactive protein (CRP), suggesting a certain influence of this inflammatory marker on cardiac risk.…”
Section: Pathophysiologymentioning
confidence: 99%
“…BNP levels ranging from 100 pg/mL to 500 pg/mL in COPD patients may be due to cor pulmonale (right ventricular stretch), moderate left ventricular failure, or both. Finally, although not specifically tested in patients with a history of COPD, BNP > 500 pg/mL is suggested by several authors to indicate acute HF in COPD patients 1,10,12,33. Recently, Macchia et al demonstrated that a BNP cutoff point of 160 pg/mL in COPD patients increases, more than 10 times, the probability of finding a ventricular dysfunction with echocardiography 8.…”
Section: Diagnosismentioning
confidence: 99%
See 1 more Smart Citation
“…Számos adat utal arra, hogy a COPD és a szívelég-telenség együttes előfordulása gyakoribb, mint ahogy prevalenciájuk alapján az várható lenne (2). A szíve-légtelenség gyakoriságáról és típusáról (szisztolés vagy diasztolés, bal vagy jobb szívfelet érintő) ellentmondásosak az adatok, ám ismert, hogy a jobbkamra-funkció károsodása rontja a COPD-s betegek prognózisát (3).…”
Section: Bevezetésunclassified
“…On the other hand, there is a large elderly population with various cardiovascular complications due to aging populations. Except for the CVDs, there are more and more age-associated chronic comorbid conditions with adverse cardiac consequences, which include type 2 diabetes mellitus, chronic obstructive pulmonary diseases, and chronic renal disease (Al-Ahmad et al, 2001;Kamalesh, 2007;Hannink et al, 2010). Therefore, it is reasonable to focus on the prevention and treatment of disorders responsible for HF.…”
Section: Epidemiology and Pathophysiology Of Hfmentioning
confidence: 99%